Description of Knowledge and Attitudes of Pregnant Women in The Third Trimester of Yoga Exercise at The Midwafe Clinic Hj.Titis Arida Suliantari Sukasari Kec.Tangerang - Yanashita Mafluha (STIKes RSPAD RSPAD Gatot Soebroto, 2024)
Yoga is a sport that pregnant women can do. Yoga exercise for pregnancy can help balance the body, mind and spirit. During pregnancy should try to stay physically healty and emotionally balanced, and can help to generate calming beliefs. From the results of the preliminary study, it was found that 7 out of 10 pregnant women in the trimester III at the midwife clinic Hj.Titis Arida Suliantari Sukasari, Kec.Tangerang with “ sufficient” knowledge in trimester III pregnant women about yoga exercise. The aim of this study is to find an overview of the knowledge of pregnant women in the trimester III of yoga exercise at the midwife clinic Hj.Titis Arida Suliantari Sukasari Kec.Tangerang in 2022. The type research used is qualitative and descriptive research design. Total sampling technique, research sample 30 person trimester III pregnant women. The variable used in this study was the single variabel instrument in this study using a questionnaire. Result shows that the level of knowledge of pregnant women in the trimester III of yoga exercise from 30 respondents in the “good” category of 11 respondents (36,7%), the “ sufficient” category namely 14 respondents (46,7%), the “lack” category namely 5 respondents (16,7%). In general, knowledge of pregnant women in the trimester III of yoga exercise is in the “ adequate” category. But not a few of them fall into the “good” and “less” categories. This needs attention, and it is hoped that pregnant women in the trimester III can care more about one of these promkes.